Pengaruh diabetes gestasional terhadap perkembangan otak janin: systematic review - Dwi Lestari, Yusri; Zerlina Elysia, Naflah (NHM PRESS, 2024)
Gestational diabetes mellitus (GDM) has been identified as having a significant impact on fetal brain development. The underlying mechanisms involve a combination of biological, environmental, and lifestyle factors. This study aims to evaluate findings from ten journal articles related to GDM and its influence on fetal brain development. A systematic review was conducted on ten selected journal articles, focusing on the effects of GDM on cognitive and motor development, structural brain changes, and risk factors exacerbating the condition. The review revealed that GDM can lead to delays in cognitive and motor development in children and structural changes in fetal brain regions associated with executive and motor functions. Factors such as oxidative stress, inflammation, maternal obesity, and high-calorie diets were found to worsen the effects of GDM through insulin resistance and disrupted neurogenesis. Additionally, poor maternal sleep quality, psychological stress, and lack of social support were shown to increase the risk of fetal developmental disorders. Intervention studies highlighted the potential to mitigate these risks through balanced diets and effective glucose management. These findings underscore the importance of a holistic approach to mitigating the adverse effects of GDM on fetal brain development. This approach includes metabolic control, healthy lifestyles, stress management, and early interventions. Further research is necessary to explore preconception prevention strategies, long-term interventions, and multifactorial influences on fetal development risks.